IMPLEMENTASI PEMBELAJARAN RQA DIPADU TPS MELALUI LESSON STUDY TERHADAP HASIL BELAJAR MAHASISWA - Hasanuddin Hasanuddin (Universitas Syiah Kuala, 2012)
The effort to master the competency can be done by creating a planned learning community, systematic, and continuous (continuous improvement). An alternative attempt to do to make continuous improvement is through Lesson Study. The purpose of this study is to determine the application of RQA learning combined by TPS through lesson study on student learning outcomes. Lesson Study conducted in three (3) stages: Plan (planning), Do (implement), and See (reflection). Subjects in the test phase the product user groups through lesson study, were 29 students (rombel 1), 3 members from the team of Plant Anatomy course, and 4 graduate students of Biology Education FKIP Syiah Kuala who has got the socialization Lesson study as an observer. Learning materials that has been agreed is: plant cells. The data analysis was conducted descriptively on the observation sheet, sheet discussions, and learning outcomes (postes), and student responses. Based on the research results, it can be concluded that: The application of RQA strategy combined with TPS through lesson study can improve student learning activity in plant cell material. Postes values shown 44.83% of students obtained A, 41.37% of students obtained B +, and 13.80% of students obtained B. Student response to the strategy that used by the implementation of lesson study is very good. Learning strategies which received is a new thing for them, make them aware about the importance of independence in learning. In addition, the learning that they follow, have been able to set up a new way of their learning, and able to evaluate the learning that they do. They agreed to implement these strategies in studying other biology course.